Stability and thermal conductivity of mono and hybrid nanoparticles dispersion in double-end capped pag lubricant - Mohd Zaki, Sharif; Wan Hamzah, Azmi; Mohd Fairusham, Ghazali; Nurul Nadia, Mohd Zawawi; Hendrawati, Tri Yuni (MDPI, 2023)
Stable nanolubricant mixtures are interrelated with thermal conductivity enhancement, thus improving heat transfer performance in automotive air conditioning (AAC) systems. This paper studies the stability and thermal conductivity of double-end capped polyalkylene glycol (PAG)-based nanolubricants specially designed for R1234yf refrigerant. Mono nanolubricants (Al2O3/PAG and SiO2/PAG) and hybrid nanolubricants (Al2O3–SiO2/PAG) were prepared using a two-step preparation method at different volume concentrations of 0.01 to 0.05%. The stability of these nanolubricants was observed by visual, UV-Vis spectrophotometer, and zeta potential. Thermal conductivity (k) was measured from 30 to 70 °C using a C-Therm thermal properties analyser. The results from the stability analysis show that all nanolubricants were confirmed in excellent stability conditions for more than six months with minimum visual sedimentation, more than 70% concentration ratio, and zeta potentials greater than 60 mV. The Al2O3–SiO2/PAG samples recorded the highest values of thermal conductivity increment, followed by the Al2O3/PAG and SiO2/PAG samples with 2.0%, 1.7%, and 1.5% enhancement. Hybrid nanolubricants have been shown to have greater potential in the AAC system because of their excellent stability and better property enhancement in thermal conductivity.